The σB-Mediated General Stress Response of Listeria monocytogenes: Life and Death Decision Making in a Pathogen - Guerreiro, Duarte N.; Arcari, Talia; O’Byrne, Conor P. (Frontiers in Microbiology, 2020)
Sensing and responding to environmental cues is critical for the adaptability and success of the food-borne bacterial pathogen Listeria monocytogenes. A supramolecular multi-protein complex known as the stressosome, which acts as a stress sensing hub, is responsible for orchestrating the activation of a signal transduction pathway resulting in the activation of σB, the sigma factor that controls the general stress response (GSR). When σB is released from the anti-sigma factor RsbW, a rapid up-regulation of the large σB regulon, comprised of ≥ 300 genes, ensures that cells respond appropriately to the new environmental conditions. A diversity of stresses including low pH, high osmolarity, and blue light are known to be sensed by the stressosome, resulting in a generalized increase in stress resistance. Appropriate activation of the stressosome and deployment of σB are critical to fitness as there is a trade-off between growth and stress protection when the GSR is deployed. We review the recent developments in this field and describe an up-to-date model of how this sensory organelle might integrate environmental signals to produce an appropriate activation of the GSR. Some of the outstanding questions and challenges in this fascinating field are also discussed.